Bottomia physics at RHIC and LHC - Wolschin, Georg (XLVI International Symposium on Multiparticle Dynamics (ISMD 2016), 2017)
In UU collisions at RHIC energies and PbPb collisions at LHC energies the suppression of ϒ mesons in the hot quark-gluon medium (QGP) versus reduced feed-down is investigated. Our model encompasses screening, collisional damping and gluodissociation in the QGP. For ϒ(1S) it is in agreement with both STAR and CMS data provided the relativistic Doppler effect and the reduced feed-down from the ϒ(nS) and χb(nP) states are properly considered. At both energies, most of the suppression for the ϒ(1S) state is found to be due to reduced feed-down, whereas most of the ϒ(2S) suppression is caused by the hot-medium effects. The role of the in-medium effects relative to reduced feed-down in creases with energy. The ϒ(1S)-suppression in PbPb at √sNN = 5.02 TeV is predicted.